5-(4-Pentylphenyl)-1,3,4-thiadiazol-2-amine - Wang, Yao (International Union of Crystallography, 2009)
The title compound, C(13)H(17)N(3)S, was synthesized by the reaction of 4-pentylbenzoic acid and thiosemicarbazide. The dihedral angle between the thiadiazole and phenyl rings is 29.9 (2)°. An intramolecular C—H⋯S interaction is observed. In the crystal, intermolecular N—H⋯N hydrogen bonding links the molecules into centrosymmetric dimers.